Learning English Vocabulary through Essential Vocabulary Application: Students’ Perceptions - Rahma Yani Rahma Yani; Benni Ichsanda Rahman Hz, (LPPM Universitas Advent Indonesia, 2026)
Technology plays an important role in English language learning, especially in vocabulary acquisition. This research is motivated by several problems faced by the students of secondary school in North Sumatra related to English vocabulary. This study aims to explore the students' perceptions of using Essential Vocabulary application to learn English vocabulary. A qualitative case study method was used, involving one class of 20 students in the eighth grade of a secondary school in North Sumatra. Students consisted of both males and females in grade eight. The data were collected through questionnaires and semi-structured interviews. The students completed a thirty-minute questionnaire and five selected students were interviewed in more depth on the use of the Essential Vocabulary app. The findings of this study revealed five main themes in students' perceptions regarding the use of the Essential Vocabulary app. The five main themes are: usability, effectiveness, interactivity, confidence and motivation, and the last is satisfaction.